Gonioscopia e tomografia de coerência óptica em pacientes com câmara anterior rasa - Esporcatte, Bruno Leonardo Barranco [UNIFESP] (2020)
This study aims to assess angular closure using gonioscopy and anterior segment optical coherence tomography (AS-OCT). Objective: To evaluate the gonioscopy performed by general ophthalmologists (GO) and glaucoma expert (GE) and AS-OCT (Visante® OCT and DRI OCT Triton®), in patients with a shallow anterior chamber. Methods: Forty-four eyes (44 patients) with shallow anterior chamber, defined by a ratio of peripheral anterior chamber depth to peripheral corneal thickness (PACD / PCT) <1⁄2 were included. Gonioscopy was performed in all subjects by two GE (GE1 and GE2) and one GO. Anterior segment imaging was obtained using Visante® OCT and DRI OCT Triton®. Agreement between examiners was assessed with the first-order agreement coefficient (AC1). Results: The mean age of participants was 65.8±9.3 years. Seven male and 37 female subjects were evaluated. Twenty-six (59%) patients had PACD / PCT <1/4 (grade I) and in 18 (41%) patients the PACD / PCT was between 1/4 and 1/2 (grade II). The agreement between GE1 and GE2 for static gonioscopy was substantial (AC1=0.63), and moderate during dynamic gonioscopy (AC1=0.56). The agreement between the GE1 and the GO was moderate (AC1=0.50) during static gonioscopy and slight (AC1=0.12) during the indentation maneuver. GE1 classified 72% of the evaluated quadrants as closed, while the GO, Visante® OCT and DRI OCT Triton® detected a closed quadrant in 68%, 58%, and 34%, respectively. There was a significant difference between all quantitative parameters obtained by AS-OCT, especially the lens vault, which showed a difference between the Visante® OCT, and the DRI OCT Triton® of 559±107 μm (p<0,001). Conclusions: The diagnostic agreement between GE and GO was moderate in static gonioscopy and poor in dynamic gonioscopy. The GE1 detected more closed quadrants than the GO and AS-OCT devices. A significant difference between parameters analyzed by AS-OCT devices was observed. Significant differences were observed between all quantitative parameters measured by Visante® OCT and DRI OCT Triton®, especially in lens vault measurement.